Fluorene and Tetraphenylsilane Based Conjugated Microporous Polymer Nanoparticles for Highly Efficient Nitroaromatics Detection in Aqueous Media - Baoping Ren; Qihao Cui; Wenyue Dong; Teng Fei (Advanced Sensor Research, 2024)
Abstract Conjugated microporous polymers (CMPs) are considered promising sensing materials for the detection of nitroaromatics. Unfortunately, the photoluminescence (PL) sensing application in water media is limited, owing to the poor solubility/dispersion in aqueous media. Here, two novel CMPs named poly(dimethylfluorene‐co‐tetrakis(4‐phenyl)silane)s (P4SiF) and poly(dimethylfluorene‐co‐tetrakis(3‐phenyl)silane)s (P3SiF) nanoparticles based on fluorene group and tetraphenylsilane unit are prepared using Suzuki coupling in water/toluene miniemulsion. P4SiF and P3SiF possess spherical particle morphology with sizes of 45 and 60 nm, respectively, and porous structure with pore diameters of both 1.9 nm. PL sensing experiments based on P4SiF and P3SiF nanoparticles in aqueous media show a sensitive and selective detection toward 2,4,6‐trinitrophenol (TNP). It is worth noting that the PL quenching effect toward TNP is not significantly changed after the addition of other nitro compounds, proving the excellent anti‐interference characteristic and highly selective detection of the polymers in water. Moreover, the t‐test indicates that the PL sensing method using P4SiF and P3SiF nanoparticles as sensing materials realizes the reliable detection of TNP in actual water samples at a 95% confidence level. Finally, the PL sensing mechanism is investigated, showing that the inner filter effect is the main factor in the PL quenching process of TNP in aqueous media.